(3eMGVQGJ aj GdfXQjGJ hGdSjGSGJ GdfbOjI (B/s - (3Hf Ydj, HdYRhRs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2017)
(3GdfXQjGJ GdfbOjI GdJbdjOjI(B- (3GdfXQjI GdcfRjI(B- (3GdfXQjI GdfbOjI GdeYGUQI(B- (3fXQjI GdJhGRf GdEbJUGOj GdYGe(B- (3GdSjGSI GdfbOjI(B- (3GdJVNe(B- (3CKQ GdEUdGM GdEbJUGOj Ydi GdSjGSI GdfbOjI aj GdLRGFQ(B- (3GfYcGS GdEUdGMGJ Ydi GdJhGRfGJ GdfbOjI(B.s
(3GdeQGLY U(B.223s
Keywords: (3GdSjGSGJ GdEbJUGOjIs; (3GdfXQjGJ GdEbJUGOjIs